Unpleasant Subjective Emotional Experiencing of Pain. - Vallath, Nandini; Salins, Naveen; Kumar, Manoj (Indian Journal of Palliative Care)
The field of pain medicine that once began as a supportive and compassionate care, adding value to the management of acute and chronic ailments, has now transformed into a vital and essential specialty with structured training programs and service units with professionals dedicating their careers to it. The expansion of understanding of the direct relationship of pain relief to the quality of life, uncovering of neuronal pathways, and technological advances in imaging as well as in interventional techniques have all contributed to this phenomenal growth. However, there is a growing concern whether the training programs and the specialized practitioners are gradually limiting their skilled inputs primarily within the sensory realm of the pain experience with sophisticated interventional techniques and relegating its subjective and emotional dimensions to perfunctory realms within the schema of service provision. While the specialty is still young, if we can understand the inherent aspect of these dimensions within the pain experience and acknowledge the gaps in service provision, it may be possible to champion development of truly comprehensive pain relief programs that responds effectively and ethically to a patient's felt needs. This article attempts to position the subjectivity of pain experience in context and surface the need to design complete systems of pain relief services inclusive of this dimension. It presents authors' review of literature on perspectives of 'unpleasant subjective emotional experiencing of the pain' to elucidate possible clinical implications based on the evidences presented on neuro-biology and neuro-psychology of the pain experience; the aim being to inspire systems of care where this dimension is sufficiently evaluated and managed.